Experimental investigation of the autoignition properties of ethanol–biodiesel fuel blends. (1st January 2019) - Kuszewski, Hubert
Highlights: Ignition and combustion delays for ethanol–biodiesel fuel blends were measured. For tested fuels, the DCN was determined. A CVCC was used during the investigation. Abstract: Growing interest in increasing the market share of renewable fuels results from the increasing consumption of fuels in various industries, especially in road transport. Such fuels include, for example, ethanol and FAME ( Fatty Acid Methyl Esters ), known as biodiesel. In diesel engines, ethanol, unlike biodiesel, cannot be directly used as a pure fuel due to its very low autoignition propensity. However, due to the good autoignition properties of biodiesel, increasing attention is being paid to the fuel constitution, for example, a blend of biodiesel with ethanol additive. This way, it is possible to obtain fuel for diesel engines that are compositions of only products of plant origin. In this paper, the autoignition properties of RME ( Rape Methyl Esters ) and ethanol blends, with the ethanol fraction up to 25% (v/v) were examined. A constant volume combustion chamber was used in the study. Under the specified test conditions, the ignition delay period and the combustion delay period, as well as the DCN ( Derived Cetane Number ), were determined for the individual blends. The average and maximum pressure rise rates in the combustion chamber were also analysed. The study has shown, for example, that with an increase of ethanol fraction in biodiesel, the periods of ignition and combustion delay increase. It was also shown that in the range from 5% (v/v) to 25% (v/v) of the ethanol fraction, for every increase in the fraction of ethanol by 5% (v/v), the DCN of the biodiesel–ethanol blend is reduced by an average of 3.4 units.